PHONOLOGICAL EVOLUTION OF OIRATA AND ITS GENETIC RELATIONSHIP WITH NON-AUSTRONESIAN LANGUAGES IN TIMOR LESTE - Mandala, Halus; Meko Mbete, Aron; Dhanawaty, Ni Made; Yos Fernandez, Inyo (e-Journal of Linguistics; Vol. 5. Januari 2011 No. 2)
Oirata (Or) as a NAN language was indicated to have a genetic relationshipwith languages in East Timor, i.e. Bunak (Bn) and Makasai (Mk) (Greenberg, 1971) andwith Mk, Fataluku (Ft) and Lovaea (Lov) (Capell, 1975). The two opinions are confusingand different from one another. Hence, an effort to trace the genetic relationship of thelanguages was made to clarify the matter. Or in Kisar Island was also assumed tooriginate from East Timor (de Jong, 1937). The native speakers should have brought withthem their language and it is believed that the acculturation and language contact with thelanguages in the surrounding areas must have occurred. This condition opened up roomfor internal and external evolution in Or.This study observed nine languages: two languages in Kisar Island and sevenin East Timor. The data were collected through interviews and face-to face conversationswith the informants who were selected by purposive sampling until a point of saturationwas reached. https://anton-nb.com The data analysis was done by using vertical-horizontal syncomparative anddiacomparative method which led to the following conclusions.Or, Ft and Mk were diachronically and convincingly proved to have a closegenetic relationship with a split patterned family tree. The Oirata-Fataluku-Makasai(OFM) group that was once the ancestor of the three languages underwent a split intoOirata-Fataluku (OF) and Mk. It means that Or is closer o Ft than Mk and at the sametime it refuted the opinions of Greenberg (1971) and Capell (1975) that Or is closer toMk.Or turned out to have undergone an internal phonological evolution as theresult of a diachronic interaction with languages that were genetically related to it in theform of: (1) vocal split */i//_#, */a//#_ and /_#; (2) vocal merger */e//_#, (3) vocalcentralization, (4) consonant split and (5) voiced stop consonant formation. The externalphonological evolution was caused by the contact with the languages in the region andOr has undergone: (1) enrichment of consonant phonemes: /b/, /c/, /d/, /j/, /g/, /ng/, /f/, /v/,and /z/, (2) formation of clusters, (3) addition of homorganic nasal stop consonantclusters: /mp/,/mb/, /nt/, /n?/, and (4) shift toward a non-vocalic language.
Keywords: language evolution, language genetic relationship, language grouping and reconstructing a protolanguage